High SARS-CoV-2 antibody levels after three consecutive BNT162b2 booster vaccine doses in nursing home residents - Marloes I Hofstee; Joanna Kaczorowska; Abigail Postema; Erna Zomer; Maren van Waalwijk; Gustaaf Jonathans; Lia GH de Rond; Gaby Smits; Lotus L van den Hoogen; Gerco den Hartog; Anne-Marie Buisman (Immunity & Ageing)
Abstract Background As older age and having certain comorbidities can influence humoral responses to vaccination, we studied antibody responses after the COVID-19 booster campaigns in nursing home (NH) residents. Methods In a two year longitudinal study with Dutch NH residents (n = 107), aged 50 years and over, we monitored antibody responses in serum prior to and after vaccination with a third, fourth BNT162b2 (wild-type; WT), and a BNT162b2 bivalent (WT/OMI BA.1) fifth vaccine. Data on vaccinations, infections, comorbidities, and, for some participants, clinical symptoms after infection were obtained with questionnaires. Data were compared to antibody responses of BNT162b2-vaccinated, healthier community-dwelling older adults (n = 32) from the general population. Results The booster vaccinations substantially increased anti-WT and anti-Omicron SARS-CoV-2 Spike S1 (S1) and Spike protein receptor binding domain (RBD)-antibody concentrations of NH residents. This resulted in comparable antibody levels between NH residents and healthier community-dwelling older adults and between infection-naïve and infected NH residents, and in a decline in treatment duration and clinical symptom severity in SARS-CoV-2-infected NH residents. Between one and twelve months after the bivalent fifth dose, anti-Omicron BA.1 antibody levels of the NH residents waned faster than those against the WT strain. Conclusions The booster vaccinations upheld humoral responses of NH residents to WT and Omicron SARS-CoV-2. This, in addition to the less virulent circulating strains, decreased symptom severity and treatment durations for SARS-CoV-2-infected NH residents. Boosting this vulnerable group should, therefore, be continued to prevent waning of humoral immunity and achieve sufficient protection especially against newly emerging variants of concern.